Differential Effects of Estrogen and Progesterone on Genetic and Environmental Risk for Emotional Eating in Women. (September 2016) - Klump, Kelly L.; O'Connor, Shannon M.; Hildebrandt, Britny A.; Keel, Pamela K.; Neale, Michael; Sisk, Cheryl L.; Boker, Steven; Alexandra Burt, S.
Recent data show shifts in genetic and environmental influences on emotional eating across the menstrual cycle, with significant shared environmental influences during pre-ovulation and primarily genetic effects during post-ovulation. Factors driving differential effects are unknown, although increased estradiol during pre-ovulation and increased progesterone during post-ovulation are thought to play a role. We indirectly investigated this possibility by examining whether overall levels of estradiol and progesterone differentially impact genetic and environmental risk for emotional eating in adult female twins ( N = 571) drawn from the Michigan State University Twin Registry. Emotional eating, estradiol levels, and progesterone levels were assessed daily and then averaged to create aggregate measures for analysis. As predicted, shared environmental influences were significantly greater in twins with high estradiol levels, whereas additive genetic effects increased substantially across low versus high progesterone groups. Results highlight significant and differential effects of ovarian hormones on etiologic risk for emotional eating in adulthood.